Data on three Baltic species of Corynosoma Lühe, 1905 (Acanthocephala: Polymorphidae) from Baltic grey (Halichoerus grypus) and ringed seals (Pusa hispida) - Leidenberger, Sonja; Boström, Sven; Wayland, Matthew (University of Skövde, 2021)
We analyzed Baltic Corynosoma material (C. magdaleni Montreuil, 1958, C. semerme (Forssell, 1904) Lühe, 1911 and C. strumosum (Rudolphi, 1802) Lühe, 1904) from grey (Halichoerus grypus) and ringed seals (Pusa hispida) for the variation of hook morphology and for finding possible morphotypes, by using the proboscis profiler (Wayland 2010) and Meristogram (Wayland 2016).

Vi analyserade material av Corynosoma material (C. magdaleni Montreuil, 1958, C. semerme (Forssell, 1904) Lühe, 1911 och C. strumosum (Rudolphi, 1802) Lühe, 1904) från gråsäl (Halichoerus grypus) och vikare (Pusa hispida) i Östersjön för variation i morfologin hos hakarna på proboscis och för att hitta möjliga morfotyper, genom att använda proboscis profiler (Wayland 2010) och Meristogram (Wayland 2016).
Data on three Baltic species of Corynosoma Lühe, 1905 (Acanthocephala: Polymorphidae) from Baltic grey (Halichoerus grypus) and ringed seals (Pusa hispida)
Keywords: Baltic Sea; Östersjön; Meristogram; Meristogram; seal; säl; Acanthocephala; Acanthocephala; Corynosoma; Corynosoma; probocis profiler; proboscis profiler; Natural Sciences; Naturvetenskap; Biological Sciences; Biologi; Zoology; Zoologi